2015
DOI: 10.1007/978-94-017-7417-8_1
|View full text |Cite
|
Sign up to set email alerts
|

The Reproductive System

Abstract: Correct sexual development is arguably the most important trait in an organism's life history since it is directly related to its genetic fitness. The developing gonad houses the germ cells, the only legacy we pass on to subsequent generations. Given the pivotal importance of correct reproductive function, it is confounding that disorders of sex development (DSDs) are among the most common congenital abnormalities in humans (Lee et al. J Pediatr Urol 8(6):611-615, 2012). Urogenital development is a highly comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
0
8
0
3
Order By: Relevance
“…Normal testicular development is considered an important prerequisite for maintaining normal reproductive function and sexual characteristics in males. 9,10 We previously found that exposure to DEHP after birth can cause testicular developmental abnormalities in Sprague-Dawley (SD) rats. One potential mechanism explaining the actions of DEHP involves oxidative stress.…”
mentioning
confidence: 99%
“…Normal testicular development is considered an important prerequisite for maintaining normal reproductive function and sexual characteristics in males. 9,10 We previously found that exposure to DEHP after birth can cause testicular developmental abnormalities in Sprague-Dawley (SD) rats. One potential mechanism explaining the actions of DEHP involves oxidative stress.…”
mentioning
confidence: 99%
“…1 Sertoli cells play an important role during testicular development, since their functions are necessary for the proper differentiation of germ cells, peritubular myoid cells and Leydig cells. 2 Leydig cells produce the testosterone 3 required for elongation of the seminiferous cords, masculinization of the reproductive tract and induction of testicular descent. 4 In humans, foetal rat testicular testosterone is detectable at 15.5 days This review will discuss effects of foetal exposure to maternal environmental challenges on male offspring fertility and normal ageing of the male reproductive system.…”
Section: Testis Developmentmentioning
confidence: 99%
“…A fase da determinação sexual se refere aos processos envolvidos no desenvolvimento do sexo gonadal, ou seja, dos eventos que culminam com a transformação da crista urogenital, que é tecido embriológico indiferenciado, para o estado de gônada bipotencial e subsequente diferenciação em gônada feminina ou masculina (3) .…”
Section: Agradecimentosunclassified
“…A etapa da diferenciação sexual engloba os processos do desenvolvimento da genitália interna e externa que resultam no fenótipo feminino ou masculino (3) .…”
Section: Agradecimentosunclassified
See 1 more Smart Citation